Effect of fat distribution on left ventricular structure and function in different sexes: a Mendelian randomization study - Li, Hang; Yin, Guangjiao; Zhang, Yanfang; Wang, Ziwei; Lv, Fang; Li, Rui; Qin, Juanjuan; Ye, Xujun (Frontiers in Endocrinology, 2025)
BackgroundAlthough there is an interaction between sex, body fat distribution, and cardiac structure and function, these relationships have not been fully elucidated yet. This study aims to reveal the causal relationship between genetic determinants of fat distribution pattern and function of the left ventricular structure in different sexes.MethodsGenetic variants for waist circumference, hip circumference, waist-to-hip ratio (WHR), and body mass index (BMI) were selected from genome-wide association studies conducted in European samples. The dataset for left ventricular (LV) parameters was obtained from over 35,000 European samples in the UK Biobank Cardiovascular Magnetic Resonance sub-study. Two-sample Mendelian randomization (MR) analysis was employed to explore causal relationships.ResultsAfter adjusting for BMI, WHR shows a positive causal relationship with LV hypertrophy and a significant negative causal relationship with LV volume and diastolic function. In further subgroup analysis, we only found similar results in WHR among the female population (FWHR), while in the male population, there was no significant causal relationship between MWHR and LV hypertrophy and diastolic function. Additionally, in our MR analysis, no causal relationship was found between WHR and LVEF.ConclusionsThis study indicates that the fat distribution pattern has unique effects on the structure and function of the LV, and these effects vary by sex. This study provides evidence for a causal relationship between fat distribution and LV structure and function across both sexes.